A new giant species of Deltochilum subgenus Deltohyboma (Coleoptera, Scarabaeidae, Scarabaeinae) from Colombia, with notes on D. spinipes Paulian, 1938 - Silva, Fernando A.b.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2014)
Deltochilum (Deltohyboma) gigante sp. nov., from Parque Nacional Las Cuevas de los Guácharos, Huila, Colombia is described based on differences in external and genital morphology. Its diagnostic characters are provided and illustrated. Lectotype and paralectotypes for D. spinipes, a close relative to the new species, are designated.